Ultrasmall tungsten phosphide nanoparticles embedded in nitrogen-doped carbon as a highly active and stable hydrogen-evolution electrocatalyst. Issue 40 (13th September 2016) - Pu, Zonghua; Ya, Xue; Amiinu, Ibrahim Saana; Tu, Zhengkai; Liu, Xiaobo; Li, Wenqiang; Mu, Shichun
Abstract : WP NPs@NC exhibits remarkable hydrogen evolution reaction catalytic activity and durability over the entire pH range. Abstract : Rational design and synthesis of highly efficient and stable non-noble metal electrocatalysts are critical for the hydrogen evolution reaction (HER) associated with some renewable energy conversion systems. Herein, we report a one-step facile synthesis of ultrasmall tungsten phosphide nanoparticles (WP NPs) embedded within a nitrogen-doped carbon (NC) matrix (WP NPs@NC). The optimized catalyst, consisting of WP NPs of less than 5 nm diameter encapsulated by ultrathin carbon shells, shows excellent HER activity in strongly acidic media with a low onset overpotential (40 mV), high current density ( j = 10 mA cm −2 at η = 102 mV), small Tafel slope (58 mV dec −1 ), and superior durability (4 days). The as-prepared WP NPs@NC catalyst also offers excellent HER activity in both neutral and alkaline conditions, as well as remarkable durability. This synthesis strategy opens up a new avenue for obtaining transition metal phosphide nanoparticles as a new class of non-noble-metal electrocatalysts for water splitting and hydrogen generation.